Insertion of Hungarian Merino Sheep Breed into the European Merino Group according to Maternal Origin (mtDNA CR) - Mária Szabó; István Monori; Szilvia Kusza (Scientific Papers Animal Science and Biotechnologies, 2023)
Merino sheep breeds have been widely distributed across the world. They represent one of the most important genetic resource of the sheep sector. But the crisis of the wool industry led to a drastic reduction in the number of European Merino breeds including the Hungarian Merino. The Hungarian Merino is a local sheep breed with a nearly 250-year old breeding history in Hungary. It has the largest number of individuals between both of the purebred (including nucleus and multiplier flocks) and commercial flocks. Most of the purebred flocks went through a liquidation after the year 1989. That also caused a drastic reduction in the number of purebred-ewes. The Hungarian Merino breeding stock consists of barely 3700 female individuals recently. This has led to declare the breed endangered in 2014. Our future plan is to analyse the genetic variability of the Hungarian Merino breed based on the approximately 1000 base pairs long mitochondrial DNA (mtDNA) D-loop sequences. So far, we collected DNA samples from 172 individuals from 10 genealogical lines. We would like to examine the haplotype diversity and compare the overall genetic distances within and among each genealogical lines. Our further plan is to compare our data to GenBank sequences of other Merino and founder breeds.